The Kimball Group reader relentlessly practical tools for data warehousing and business intelligence - Kimball, Ralph; Ross, Margy 1959-; Becker, Bob 1954-; Mundy, Joy 1961-; Thornthwaite, Warren 1957- (John Wiley & Sons, Inc., 2016)
Offers a collection of recommended guidelines for data warehousing and business intelligence. Features articles covering the complete lifecycle of data warehousing, including project planning, requirements gathering, dimensional modeling, ETL, and business intelligence and analytics